THE USE OF NEEDLE DECOMPRESSION PROCEDURES IN NEONATES TENSION PNEUMOPERITONEUM: A CASE REPORT - Pitaloka, Dyah; Purawijaya, Handrian; Permatasari, Novita Indah; Husna, Ismalia (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2023)
Abstract: The Use of Needle Decompression Procedures in Neonates Tension Pneumoperitoneum: A Case Report. Tension pneumoperitoneum is the emergence of free air in the peritoneal cavity. There are various causes of tension pneumoperitoneum. Needle decompression is a temporary emergency measure that can be performed in patients with tension pneumoperitoneum to reduce intra-abdominal pressure. A baby boy born by cesarean section from G2P1A0 36 weeks pregnant woman with an indication of 48 hours of membrane premature rupture. 1 day after birth from the results of the abdominal X-ray appears a free air in radiologic finding. The patient then underwent needle decompression for tension pneumoperitoneum because surgery could not be performed immediately due to limited supporting facilities. Needle decompression is an effective temporary emergency measure to reduce intra-abdominal pressure in tension pneumoperitoneum patients.